2024
DOI: 10.3390/jcm13020315
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Inflammation and Infection: Key Microbiological and Immunological Aspects

Kayle Dickson,
Juan Zhou,
Christian Lehmann

Abstract: The urinary system, primarily responsible for the filtration of blood and waste, is affected by several infectious and inflammatory conditions. Focusing on the lower tract, this review outlines the physiological and immune landscape of the urethra and bladder, addressing key immunological and microbiological aspects of important infectious/inflammatory conditions. The conditions addressed include urethritis, interstitial cystitis/bladder pain syndrome, urinary tract infections, and urosepsis. Key aspects of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 199 publications
0
2
0
2
Order By: Relevance
“…Н еускладнений цистит визначається як гострий, спорадичний або рецидивний, що виникає у невагітних жінок без анатомічних та функціональних порушень сечових шляхів або супутніх захворювань [1,2].…”
Section: Assessment Of Chronometric Indicators Of the Speed Of The On...unclassified
See 1 more Smart Citation
“…Н еускладнений цистит визначається як гострий, спорадичний або рецидивний, що виникає у невагітних жінок без анатомічних та функціональних порушень сечових шляхів або супутніх захворювань [1,2].…”
Section: Assessment Of Chronometric Indicators Of the Speed Of The On...unclassified
“…Інфекції сечових шляхів (ІСШ) значно поширені у всьому світі. Від бактеріального ураження сечового тракту щороку страждає близько 150 млн людей [2,3]. Результати досліджень свідчать, що до 18-20 років принаймні один епізод гострого циститу розвивається у 20% дівчат, у 25-40% жінок після епізоду гострого циститу протягом року розвивається рецидив, причому у 50% -понад 3 разів на рік [4,5].…”
Section: Assessment Of Chronometric Indicators Of the Speed Of The On...unclassified
“…Urosepsis, a severe condition caused by severe UTI that leads to organ failure, is an important cause of sepsis [11]. Approximately 30% of the sepsis cases in the United States are attributable to UTI [12]. Gharbi et al [13] found that owing to physiological tendencies, such as the decline of the immune system, as well as the presence of chronic diseases that alter immune function, such as diabetes and chronic kidney failure, elderly populations diagnosed with urosepsis have more severe conditions, and these diseases are associated with higher mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…UPEC is a Gram-negative rod bacterium belonging to Enterobacteriaceae family in the phylum Pseudomonadota. The pathogenesis of UPEC UTIs has been previously reviewed ( Flores-Mireles et al., 2015 ; Dickson et al., 2024 ). UPEC is a commensal residing in the gut.…”
Section: Introductionmentioning
confidence: 99%